Pengaruh Kompetensi SDM Terhadap Kinerja Pegawai Rumah Sakit Umum Daerah H.M Djafar Harun Kolaka Utara - Futri Aulya Alwi; Agung Widhi Kurniawan; Uhud Darmawan Natsir; Romansyah Sahabuddin; M. Ikhwan Maulana Haeruddin (CV. Lafadz Jaya, 2023)
The Influence Of Human Resources Competence On Employee Performance At H.M Djafar Harun Kolaka Regional General Hospital Kolaka Utara Supervised by Mr. Agung Widhi Kurniawan and Mr. Uhud Darmawan Natsir. This study aims to determine the effect of HR competence on employee performance at the H.M Djafar Harun Regional General Hospital, North Kolaka. The population in this study were all employees of the H.M Djafar Harun Kolaka Utara 208 Regional General Hospital. Sampling in this study used sample calculations with the Slovin formula where after passing the calculations a total sample of 67 employees was taken with the type of quantitative research. Data collection techniques in this study This study uses observation, questionnaires and documentation with simple linear regression analysis techniques.The results of the study show that there is a positive and significant influence of competence as a whole on employee performance with a presentation of 0.188%. This implies that the bond variable (employee performance) can be interpreted by the HR competency system by 0.188%.